2006
DOI: 10.1182/blood.v108.11.2565.2565
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Hematopoietic Stem Cells (HSC) from Cord-Blood (CB) Derived Mononuclear Cells (MNC) in Cytokine-Free Environment Using Mesenchymal Cells Spatial Co-Culture System.

Abstract: In situ, HSCs are intimately associated with discrete spatially organized niches within the bone marrow, which are part of the “hematopoietic inductive microenvironment” (HIM). The HIM provides a range of molecular signals that collectively control HSC differentiation and self-renewal. This process is mediated via cell-cell and cell-ECM molecular contacts or through specific factors synthesized and secreted by mesenchymal stromal cells (MSC). Current strategies aimed at ex vivo expansion of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One of the key challenges in utilizing cord blood HSCs for bone marrow transplantation (BMT) is the limited number of CD34 + cells. Clinical outcomes have indicated that successful engraftment correlates with higher numbers of CD34 + cells (5,37,38). Recent clinical trials have underscored the importance of developing effective methods for expanding HSCs in vitro, potentially overcoming the limitations associated with cord blood HSC numbers for adult BMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key challenges in utilizing cord blood HSCs for bone marrow transplantation (BMT) is the limited number of CD34 + cells. Clinical outcomes have indicated that successful engraftment correlates with higher numbers of CD34 + cells (5,37,38). Recent clinical trials have underscored the importance of developing effective methods for expanding HSCs in vitro, potentially overcoming the limitations associated with cord blood HSC numbers for adult BMT.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is the main protein found in bone marrow ECM (47). Collagen gel scaffolds based can help to improve CD34 + HSCs reconstitution (37). Natural DBM scaffold is easy to make; it is widely available and composed of natural ECM (33).…”
Section: Discussionmentioning
confidence: 99%